Exploration of Non-compliance of Micro, Small and Medium Business Taxpayers: Phenomenology Study - Umi Nandiroh (JEMAP, 2021)
This study aims to describe the meaning of non-compliance with taxes, especially for taxpayers of small and medium enterprises. The background of this research is that there is a phenomenon that is not all taxpayers' fulfill their tax obligations in accordance with the provisions of tax regulations. Resistance that occurs in carrying out tax obligations depends on how tax interpreters interpret non-compliance. This study used a qualitative approach with the Schutz interpretive phenomenology as a research method. The phenomenology method focuses on the object of exploration to gain knowledge. Data was obtained through interviews with small business taxpayers. This study found the motives of taxpayers in carrying out their tax obligations. Which consisted of six elements, namely:  situations those were dilematic, opportunistic, distrust, injustice, not willing, and saving yourself. The motive must be found first, because based on Schutz's interpretive phenomenology method, someone will interpret something depending on the motive in interpreting something. From the motives that have been known, it can be concluded that in order to carry out their tax obligations, taxpayers need trust, both for the government, and for God.